Timing of form-focused instruction: Effects on EFL learners’ grammar learning - Xu, Jinfen; Li, Changying (Studies in Second Language Learning and Teaching, 2022)
This study investigates how different form-focused instruction (FFI) timing impacts English as a foreign language (EFL) learners’ grammar development. A total of 169 Chinese middle school learners were assigned to four conditions randomly: control, before-isolated FFI, integrated FFI, and after-isolated FFI. The three experimental groups received treatments which combined form and meaning with the English passive voice as the teaching target, but learners’ attention was drawn to the passive voice with different timing. The before-isolated and after-isolated groups received the treatment before and after communicative activities, respectively. For the integrated FFI group, intervention occurred during communicative activities. A picture writing test and a written error correction test were employed to measure students’ performance. The results indicated that the three experimental groups manifested significant improvement. Before-isolated FFI produced the best immediate and delayed effects, and integrated FFI produced better immediate effect than after-isolated FFI, while after-isolated FFI produced better delayed effect than integrated FFI. The findings indicated that pedagogical sequences in FFI are important, and teachers might need to guide adolescent learners to focus on form explicitly before communicative activities.